Multiple Access Methods to Hierarchically Structured Full Text Databases - Shepherd, M.A.; Watters, C.R.; Grundke, E.W.; Bodorik, P. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2022)
see PDF